Implementation of VIKOR Method in Determining Recipients of Cash Direct Assistance in Kalimas Village - Sy Kamal Baraqbah; Rahmi Hidayati; Irma Nirmala (CESS (Journal of Computer Engineering, System and Science), 2022)
Kalimas Village is one of the villages located in Sungai Kakap, Kubu Raya Regency, West Kalimantan. Kalimas Village is one of the villages that seeks to restore the welfare of the people in overcoming poverty cases which are global cases. Direct Cash Assistance (DCA) is one of the efforts made by Kalimas Village Officials in restoring the welfare of the people by providing assistance to underprivileged communities, especially those who have never received any kind of assistance from the government. However, the selection and determination process is still done manually so it takes a relatively long time, and sometimes the assessment is still subjective in making the selection and determination. The VIKOR method is one method that can be a solution in the process of determining the recipients of DCA funds. VIKOR method will calculate the value of each criterion used in the determination so as to provide accurate and optimal ranking results based on the weights and criteria used. The test results of 30 DCA candidates show that the VIKOR method can provide recommendations for DCA recipients with the best VIKOR 0.010798 owned by candidate K21 with 0.5 veto.